Minimally invasive surgery for spinal fractures due to multiple myeloma - Rui Reinas; Djamel Kitumba; Leopoldina Pereira; Oscar L Alves (Journal of Craniovertebral Junction and Spine, 2021)
Background: Multiple myeloma (MM) presents with spinal lesions in 60% of cases. The combination of osteolytic lesions with multifactorial osteopenia raises specific surgical treatment challenges. Minimally invasive spine surgery (MISS) could be a potential option for MM spinal lesions treatment. Objective: The objective of this study is to evaluate MISS techniques to treat patients presenting with spine fractures due to MM Methods: Retrospective analysis of consecutive patients with histology-proven pathological fractures caused by MM treated with MISS between 2009 and 2018. We collected the data from the clinical records on epidemiology, topography of spine lesions, surgical techniques, blood loss, operation time, complications, mean in-hospital time, and clinical evolution. Results: Twenty-one patients were studied – 13 males and 8 females, with a mean age of 64 years (range 43–83). Mean preoperative spinal instability neoplastic score was 9.8 ± 6 (range 5–16). All cases had a thoracolumbar location – 15 patients underwent kyphoplasty (KP) or vertebroplasty (VP) and 6 were treated with other more complex procedures. All patients had a reduction of pain and/or analgesic load. Vertebral body height increased by a mean of 2.9 mm after VP/KP. Mean hospital stay was 1.3 days for KP/VP and 5.0 days for other MISS procedures. Three patients had complications. Conclusions: The heterogeneity of techniques used reflected the variety of spine involvement by MM. KP and VP led to shorter hospital stays and less complications, being adequate for lesions without major instability. More complex MISS techniques offer an effective treatment with short delay for starting MM adjuvant treatment.